The Effect of Teaching Experience of Productive Teachers on Pedagogical Competence at SMK Negeri 4 Takalar - Nurul Istiqamah; Udin Sidik Sidin; Iwan Suhardi (Journal of Educational Studies in Science, Technology, Engineering, Arts and Humanities, 2026)
A teacher's teaching experience is the period of time a teacher performs the duties of a teacher at a particular educational institution. This is based on a letter of assignment or employment contract issued by an authorized educational institution, such as a school, university, or other educational institution. SMK Negeri 4 Takalar is a vocational high school with five (5) expertise programs with vocational teachers in several departments who are still ongoing and fresh graduates due to a shortage of productive teachers. The purpose of this study was to examine the effect of productive teachers' teaching experience on the pedagogical competence of SMK Negeri 4 Takalar. This was a correlational study using a descriptive quantitative approach. Data collection methods included questionnaires, documentation, and interviews. The study population consisted of all 17 productive teachers. Data analysis techniques included simple linear regression analysis. The results showed that the total recapitulation of respondents' answers on the teaching experience variable from the four indicators observed by the researcher was 55%, and the total recapitulation of respondents' answers on the pedagogical competence variable from the five indicators observed by the researcher was 47%. The simple linear regression test on the regression coefficient equation values of the two variables showed a significant influence. The correlation between the two variables was strong. The hypothesis test obtained a t-count for the teaching experience variable that was greater than the t-table, so this study concluded that the teaching experience of productive teachers had a significant effect on pedagogical competence at SMK Negeri 4 Takalar.